Implementation of Strengthening Values of Nationalism in Character Education Through History Learning In Public Senior High School 1 Sungai Penuh - Alfurkon Adli; Siti Fatimah (Postgraduate School, Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this study was to determine the implementation of strengthening the values ​​of nationalism in character education through learning history in senior high school 1 Sungai Penuh. The implementation of nationalism values ​​in character education which is the study in this study is the planning of the implementation of historical learning based on nationalism values ​​as outlined in the implementation of learning plans by teachers, the implementation of national values-based learning through classroom learning activities and constraints faced by teachers in the implementation of historical learning based on the values ​​of nationalism in character education. This study uses a qualitative approach with a type of descriptive research. The subject of this study was the deputy head of the curriculum in the field, history teacher who taught Indonesian history subjects in class XI and several students of class XI. Data collection techniques used in the study were interviews, observation and documentation. The data analysis technique used in this research is the analysis of Miles and Huberman data, namely collecting data, reducing data, displaying data and drawing conclusions. The technique of checking the validity of the data used in this study is the data triangulation technique. Based on the results of the study found that the planning of the implementation of historical learning based on nationalism values ​​in character education has been integrated by the teacher into the RPP then the implementation of the core learning activities of the teacher has instilled nationalism values ​​by giving real examples in real life in accordance with the material discussed. In implementing nationalism values ​​in character education through history education also encountered obstacles faced by teachers such as insufficient time and also bad environmental factors that make it difficult for teachers to exemplify or instill national values ​​for students.